Accessible catalyst pore volumes, for water and organic liquids, as probed by NMR cryoporometry - Webber, John Beausire Wyatt (Diffusion Fundamentals, 2014)
Chemical reaction speed is frequently enhanced at a surface, particularly when materials like platinum are present. It is well known that porous materials such as sol-gel silicas, controlled pore glasses, templated porous materials such as SBA-15, MCM-41, MCM-48, and zeolites, offer large surface areas. This in turn makes them ideal for catalysing chemical reactions. Thus an important use for porous materials is as a substrate and media to promote chemical reactions. However small pores are not always easily accessed by some of the organic liquids in which these catalytic reactions ideally take place. Cryoporometric techniques offer the possibility of directly probing the fraction of a pore that is actually accessible to a probe liquid. This fractional volume has significant impact on the catalytic efficacy of a particular solvent that is used to promote a reaction in the pores. Pore size, pore geometry, pore throat, pore surface material (hydrophilic/hydrophobic) and choice of probe liquid all influence the accessible fraction. By performing an NMR cryoporometric measurement using a particular liquid of interest, it is possible to directly access this information, which is of prime importance for catalysis, and financially very significant on an industrial scale. Results are reported here for a set of liquids, some simple alkanes (dodecane, tetradecane and hexadecane) plus water and cyclohexane, accessing pores in sol-gel silicas of nominal pore diameters 60Å, 100Å, 200Å, 500 Å. The key conclusions were that for the alkanes, the dimension of chain length was not relevantto the filling fraction, however for the cyclohexane a molecular diameter of 3.8 Å fitted the data well.